The Concept, Policy and Implication of Environtmental Sustainability in Islamic Universities in Indonesia - Mustofa, Imam; Syarifudin, Ahmad; Muntoha, Tohir (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
One example of great achievement in Islamic studies in Indonesia is the integration and interconnection of numerous disciplines of knowledge through Islamic institutions. This method has been concretized over the last two decades by transforming Islamic institutes into universities, allowing them to extend numerous scientific areas, notably social humanities and science, by merging them with Islamic studies. When the modern era's environmental problem has impacted practically every country around the globe, including Indonesia, the question is how Islamic colleges may help alleviate the environmental crisis through an integrative-interconnected strategy. This research investigates the concepts, methods, and actual tactical measures undertaken by Islamic universities in Indonesia, as well as their significance in the fight against environmental issues. The study is based on qualitative data obtained from the State Islamic University (UIN) of Raden Intan Lampung. The study's findings show that the conceptualizations and strategies of Indonesian Islamic institutions are situated in the context of addressing the environmental crisis. The concept has advanced to the level of environmental conservation curriculum. Similarly, at the policy level, it has been employed for spatial planning and campus infrastructure development. However, because these stages are still internal, there are no concrete consequences or impacts. The efforts of Islamic institutions in Indonesia have not been successful in resolving the country's environmental issues. Salah satu contoh pencapaian besar studi Islam di Indonesia adalah integrasi dan interkoneksi berbagai disiplin ilmu melalui lembaga-lembaga Islam. Metode ini telah dikonkretkan selama dua dekade terakhir dengan mengubah institut Islam menjadi universitas, yang memungkinkan mereka memperluas berbagai bidang ilmiah, terutama humaniora sosial dan sains, dengan menggabungkannya dengan studi Islam. Ketika masalah lingkungan era modern telah berdampak pada hampir setiap negara di dunia, termasuk Indonesia, pertanyaannya adalah bagaimana perguruan tinggi Islam dapat membantu meringankan krisis lingkungan melalui strategi yang saling berhubungan dan integratif. Penelitian ini mengkaji konsep, metode, dan langkah taktis aktual yang dilakukan universitas Islam di Indonesia, serta signifikansinya dalam melawan isu lingkungan. Kajian ini didasarkan pada data kualitatif yang diperoleh dari Universitas Islam Negeri (UIN) Raden Intan Lampung. Temuan studi menunjukkan bahwa konseptualisasi dan strategi lembaga Islam Indonesia terletak dalam konteks mengatasi krisis lingkungan. Konsep tersebut telah maju ke tingkat kurikulum pelestarian lingkungan. Demikian pula di tingkat kebijakan, telah digunakan untuk perencanaan tata ruang dan pembangunan infrastruktur kampus. Namun, karena tahapan-tahapan tersebut masih bersifat internal, tidak ada konsekuensi atau dampak yang nyata. Upaya lembaga-lembaga Islam di Indonesia belum berhasil menyelesaikan masalah lingkungan negara.